2023
DOI: 10.7759/cureus.46826
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relation Between Asthma Severity and Serum Vitamin D Levels: A Cross-Sectional Study

Navjot Kaur,
Vipul Kumar,
Jagjot Singh
et al.

Abstract: IntroductionVitamin D3's importance for bone health in children and its potential role beyond musculocutaneous health is an ongoing area of research. This study assesses vitamin D3 deficiency prevalence in asthmatic children and its correlation with asthma cases and healthy controls. MethodsThis cross-sectional study was conducted in a tertiary care hospital in Punjab, India among children between 5 and 15 years of age. Fifty children diagnosed with "bronchial asthma" who were under follow-up in the asthma cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Vitamin D levels in peripheral blood are low in patients with systemic sclerosis [ 10 ]. Importantly, vitamin D deficiency has been linked to the increase in asthma incidence over the past 20 years [ 11 13 ]. Extensive epidemiological studies have shown that vitamin D supplementation can enhance the antiviral response of respiratory epithelial cells [ 14 ] and inhibit IL-17 A secretion in the peripheral blood of severe asthma patients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D levels in peripheral blood are low in patients with systemic sclerosis [ 10 ]. Importantly, vitamin D deficiency has been linked to the increase in asthma incidence over the past 20 years [ 11 13 ]. Extensive epidemiological studies have shown that vitamin D supplementation can enhance the antiviral response of respiratory epithelial cells [ 14 ] and inhibit IL-17 A secretion in the peripheral blood of severe asthma patients [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%